Coping strategies and education of parents of autistic children in Bangladesh (Bangladesh Journal of Medical Science, 2020)
Objectives: Bangladesh is a country characterized by the shared cultures of different ethnic groups. Parents in different cultures demonstrate diverse psychological functioning when caring for a child with a chronic disability such as autistic disorder. Few investigations have been conducted in Bangladesh regarding the coping strategies used by parents of autistic children. Therefore, the purpose of this study was to examine the coping strategies of parents raising autistic children in Dhaka city. We also studied the relation between the coping strategies of parents with autistic children and the parents’ educational status.Materials and Methods: A total of 44 parents with autistic children participated in this survey and were randomly selected from a simple sample comprising parents of children attending special schools in Dhaka city, Bangladesh. Data were collected through questionnaires on coping strategies and were administered by an interviewer. A chi square test was conducted to determine the significance of the relation between education and different coping strategies.Results and Discussion: Eight groups of coping strategies were selected as follows: Confrontive coping, Distancing from problem, Seeking social support, Self-controlling, Accepting responsibility, Planful problem-solving, Escape-avoidance, and Positive reappraisal. A total of 34, 10, 26, 19, 17, 32, 6, and 35 parents chose “at least try,” “not overanalyzing,” “get professional help,” “separate own feelings,” “conduct self-evaluation” “apply more effort….;” “hand over…,” “fantasies for turn the….,” “wish for over the…,” and “change daily lifestyle”, respectively. Moreover, a significant relation was revealed between parents’ education and the strategy, “accepting responsibilities.”Conclusion: We concluded that parents of autistic children need more social support, counseling, and higher education to support their child’s special needs, as well as ensure their own physical and mental wellbeing.Bangladesh Journal of Medical Science Vol.19(4) 2020 p.614-619